A Hybrid Cryptographic and Biometric Framework for Real-Time Signer Verification in Digital Signing Systems - Yulianti, Farah (Ridwan Institute, 2026)
Digital document signing systems are widely adopted to support legally binding electronic transactions by ensuring practicality, integrity, authenticity, and non-repudiation in electronic workflows. Current digital signing platforms rely on public key Infrastructure (PKI) combined with secondary verification mechanisms such as one-time password (OTP) delivered via email, SMS, or messaging applications to strengthen signer authentication. While OTP mechanisms provides additional account level security, they primarily verify control over a communication channel and do not guarantee the individual performing the signing action is physically present or intentional participation of the signer at the time of document execution. This limitation creates potential vulnerabilities in cases of communication channel compromise. This paper investigated the security limitations of OTP based signer verification in digital signing environments and proposes a hybrid framework that integrates cryptographic signatures, OTP verification, and gesture-based facial liveness detection. The objective is to bind the signing action to real-time human presence while preserving the integrity guarantees of PKI. The results indicate that while OTP only verification maintains high usability, it is vulnerable under simulated channel-compromise conditions. Biometric liveness detection reduces presentation attack success, and the hybrid configuration demonstrates improved resistance to unauthorized signing compared with OTP only verification. These findings suggest that integrating lightweight biometric liveness detection into digital signing workflows can enhance identity assurance without replacing existing PKI infrastructure. This paper contributes to the discussion on strengthening signer legitimacy in electronic document execution through multi-layer identity verification.